ORGANIZACION Y VARIACIONES ESTACIONALES DEL ÁPICE VEGETATIVO DEL ALCORNOQUE - Molinas, M; Oliva, P; Vázquez, M Oliva P (Scientia gerundensis, 1989)
This paper is directed to the basic understand of organization and seasonal changes in the vegetative buds of the cork-oak through the study of the phenology and the histology of a branch during to annual cycles. During the period under study, two sprouting seasons succeded each year; one sprouting was allways in the middle of the spring and the other one either in the summer or in the fall. The elongation of the branch segments was characteristic of a cork-oak in juvenil phase. The hight value of the whole growth should be noticed. The cork oak produces both short and long shoots. Long shoots occur at the apex and distal portions of branches. The long and short shoots differ in number of leaves but not in internode elongation. Elongation depend on the shoot vigor and position. There is a good correlation between elongation and number of leaves per segment. Buds show seasonal changes. A rest phase, a bud expansion phase and a new bud formation phase partially omerlaping the bud expansion phase can be distinguished. Cork-oak vegetative buds show a tunica and corpus type of cellular zonation which corresponds to the Type I of the Gifford and Carson (1971) classification. Only lowermost leaves ovenvinter in the bud. This may explain the maked heteroblastia of the leaves in the shoots. The seasonal study shows that maximum cytohistological zonation occurs near the end of rapid shoot elongation.
Keywords: bud morphology; cork-oak; Phenology; Quercus suber; shoot elongation